Oxidative transformation of emerging organic contaminants by aqueous permanganate: Kinetics, products, toxicity changes, and effects of manganese products. (15th September 2021) - Li, Juan; Pang, Su-Yan; Wang, Zhen; Guo, Qin; Duan, Jiebin; Sun, Shaofang; Wang, Lihong; Cao, Ying; Jiang, Jin
Highlights: Reactivity towards Mn(VII) decreases in order of olefins >phenols >amines at pH 7.0 Products, reaction pathways, and toxicity changes of EOCs oxidation by Mn(VII) are reviewed Manganese products enhance Mn(VII) oxidation via oxidative and catalytic effects Effects of solution pH, NOM, cations, and anions on Mn(VII) oxidation are summarized Destruction of functional groups of EOCs by Mn(VII) generally decreases the toxicity Abstract: Permanganate (Mn(VII)) has been widely studied for removal of emerging organic contaminants (EOCs) in water treatment and in situ chemical oxidation process. Studies on the reactive intermediate manganese products (e.g., Mn(III) and manganese dioxide (MnO2 )) generated from Mn(VII) reduction by EOCs in recent decades shed new light on Mn(VII) oxidation process. The present work summarizes the latest research findings on Mn(VII) reactions with a wide range of EOCs (including phenols, olefins, and amines) in detailed aspects of reaction kinetics, oxidation products, and toxicity changes, along with special emphasis on the impacts of intermediate manganese products (mainly Mn(III) and MnO2 ) in-situ formed. Mn(VII) shows appreciable reactivities towards EOCs with apparent second-order rate constants ( k app ) generally decrease in the order of olefins ( k app  = 0.3 - 2.1 × 10 4 M −1 s −1 ) > phenols ( k app  = 0.03 - 460 M −1 s −1 ) > amines ( k app  = 3.5 × 10 −3 - 305.3 M −1 s −1 ) at neutral pH. Phenolic benzene ring (for phenols), (conjugated) double bond (for olefins), primary amine group and the N-containing heterocyclic ring (for amines) are the most reactive sites towards Mn(VII) oxidation, leading to the formation of products with different structures (e.g., hydroxylated, aldehyde, carbonyl, quinone-like, polymeric, ring-opening, nitroso/nitro and C-N cleavage products). Destruction of functional groups of EOCs (e.g., benzene ring, (conjugated) double bond, and N-containing heterocyclic) by Mn(VII) tends to decrease solution toxicity, while oxidation products with higher toxicity than parent EOCs (e.g., quinone-like products in the case of phenolic EOCs) are sometimes formed. Mn(III) stabilized by model or unknown ligands remarkably accelerates phenolic EOCs oxidation by Mn(VII) under acidic to neutral conditions, while MnO2 enhances the oxidation efficiency of phenolic and amine EOCs by Mn(VII) at acidic pH. The intermediate manganese products participate in Mn(VII) oxidation process most likely as both oxidants and catalysts with their generation/stability/reactivity affecting by the presence of NOM, ligand, cations, and anions in water matrices. This work presents the state-of-the-art findings on Mn(VII) oxidation of EOCs, especially highlights the significant roles of manganese products, which advances our understanding on Mn(VII) oxidation and its application in future water treatment processes. Graphical abstract: Image, graphical abstract